(untitled) (Research, Society and Development, 2021)
Granuloma annulare (GA) is a granulomatous inflammatory disease, considered benign, but of uncertain etiology. GA is associated with several conditions, such as diabetes mellitus, malignancy, in addition to other conditions and medications. The present article is a cross-sectional, observational and retrospective study whose objective was to analyze the association between the types of AG and antihypertensive drugs used by patients before the onset of this lesion. We also propose to investigate the associations with certain comorbidities (hypertension, diabetes, dyslipidemia, leprosy and malignancy), as well as to map the most affected areas of the body. The main result was the statistically significant association between the use of atenolol and the disseminated clinical type (p=0.024) and the association of the localized clinical type with losartan (p=0.0604). Despite the intriguing results, more robust studies of these associations are needed in order to establish definitive conclusions.